(untitled) (London Journal of Research In Management & Business, 2025)
This study aims to highlight the role of security in the performance of MTN Ivory Coast promoter agents. It focuses on a sample of three MTN network promoters residing in the municipalities of Koumassi, Adjam and Yopougon. These promoters were subjected to the interview technique. The data from this operation were analyzed and followed by a synthesis. This reveals to us that security at the level of promoters and technical services play a key role in the performance of Momo Data promoters at MTN. This study recommands that managers of all compagnies take into account individual and IT security in oder to achieve satisfactory results.